2022
DOI: 10.1007/s11356-022-22888-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and metal resistance of Stenotrophomonas maltophilia isolates from Eboling permafrost of the Tibetan Plateau

Abstract: There is a growing concern about antibiotic and metal resistance in natural and clinical settings. This study examined antibiotic and metal resistance for ancient Stenotrophomonas maltophilia isolated from permafrost. Whole-genome sequencing was applied to examine antibiotic resisrance genes and metal resistance genes. The permafrost S. maltophilia exhibited resistance to chloramphenicol, trimethoprim-sulfamethoxazole, and erythromycin, which is consistent with the presence of multidrug e ux pump smeDEF. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Interestingly, research has shown that some innately resistant environmental bacteria, such as S. maltophilia , can metabolize the carbon from antimicrobial agents to aid in growth ( Martinez, 2008 ) ( Dantas et al., 2008 ). Additionally, a truncated phosphoglucosamine mutase, encoded by glmM , indirectly counters the effects of antibiotics that target bacterial cell wall peptidoglycan ( Avison et al., 2001 ), and the qnr gene protects bacteria from quinolone antibiotics targeting DNA gyrase and topoisomerase ( Zhang et al., 2023 ). However, prevalence of most of these resistance factors is unknown.…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, research has shown that some innately resistant environmental bacteria, such as S. maltophilia , can metabolize the carbon from antimicrobial agents to aid in growth ( Martinez, 2008 ) ( Dantas et al., 2008 ). Additionally, a truncated phosphoglucosamine mutase, encoded by glmM , indirectly counters the effects of antibiotics that target bacterial cell wall peptidoglycan ( Avison et al., 2001 ), and the qnr gene protects bacteria from quinolone antibiotics targeting DNA gyrase and topoisomerase ( Zhang et al., 2023 ). However, prevalence of most of these resistance factors is unknown.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…S. maltophilia can also grow in the presence of most heavy metals such as copper, zinc, cobalt, nickel, mercury, silver, antimony, tellurite, selenite, lead, and molybdenum among other metals ( Pages et al., 2008 ; Deredjian et al., 2016 ; Yu et al., 2018 ; Zhang et al., 2023 ). For instance, S. maltophilia strain D457R, a multiresistant derivative of clinical isolate D457, displays cadmium resistance due to the cadmium efflux pump encoded by cadA ( Pages et al., 2008 ).…”
Section: Metal Resistancementioning
confidence: 99%